Asset Inequality Matters: An Assessment of the World Bank's Approach to Poverty Reduction. - Birdsall, Nancy; Londoño, Juan Luis (American Economic Review, 1997)
The fight against poverty has been adopted by the multilateral development banks as their principal objective. Almost three decades after Robert McNamara announced that the World Bank's fundamental work was to improve the lives of the poor, its new president, James Wolfensohn, has reiterated that poverty reduction is the World Bank's principal purpose. Similarly, in 1994 the Inter-American Development Bank set social progress and social equity as its central objective. The emphasis in the international institutions contrasts with disappointing results in the real world. Although life expectancy, school enrollmuent, and other indicators of social wellbeing have improved dramatically across the developing world, and although the proportion of the poor has declined in the last few decades, the absolute number of poor people in the world has actually increased. Today about 1.3 billion people in less developed countries still subsist on less than $1 per day (World Bank, 1980, 1990, 1996). The case of Latin America is dramatic. While in the 1970's the number of poor fell, it nearly doubled in the 1980's, increasing from about 80 to almost 150 million; and in the last few years, the number of poor, now 33 percent of the total population, has failed to fall despite economic recovery (Birdsall and Londofio, 1997). The contrast between the multilateral banks' goals and these disappointing results suggests the need for a critical reassessment of their approach to poverty reduction. In this paper we describe the approach reflected in the work of World Bank economists and, based on new empirical work, assess its relevance for Latin America.'